Hubungan Gaya Belajar dan Keterampilan Belajar dengan Hasil Belajar Mahasiswa Serta Implikasinya dalam Pelayanan Bimbingan dan Konseling di Fakultas Ilmu Pendidikan Universitas Negeri Padang - Zahri, Triave Nuzila; Yusuf, A Muri; S, Neviyarni (Universitas Negeri Padang, 2017)
The learning process in university level is quite different from the former education levels so that the students need to be adapted to. The students, in fact, were still unaccustomed to the learning style, unserious and frequently absent from the class, did not do assignment as they were required, and did not submit the tasks on the time they were due. This research was intended to describe the students’ learning style and learning skill and its implication in Guidance and Counseling service. This research could be classified into descriptive study. The population of the research was 1021 students in the Faculty of Education of UNP. By using purposive random sampling technique and Taro Yamane formula, 287 students were taken as the sample. The instrument of the research was the scale of Likert model. The data obtained were analyzed by using percentage technique. The correlation between learning style and learning outcomes was tested by using Chi Square, and correlation between learning skill and learning outcomes was tested by using Spearman Rank Correlation. The results of the research revealed that: (1) the learning style dominantly applied by the students of the Faculty of Education of UNP was visual learning style which was used by 49.13% students, (2) the learning skill of the students of the Faculty of Education of UNP was in average category (68.18%), (3) there was a significant correlation between learning style and learning outcomes, and (4) there was a significant correlation between learning skill and learning outcomes. The implication of these research findings toward Guidance and Counseling Service was it was necessary to cooperate with other related parties to optimize the students’ learning style, learning skill and learning outcomes.